Tropical field stations yield high conservation return on investment - Eppley, Timothy M.; Reuter, Kim E.; Sefczek, Timothy M.; Tinsman, Jen; Santini, Luca; Hoeks, Selwyn; Bitariho, Robert; Andriantsaralaza, Seheno; Shanee, Sam; DiFiore, Anthony (Conservation Letters, 2024)
Conservation funding is currently limited; cost-effective conservation solutions are essential. We suggest that the thousands of field stations worldwide can play key roles at the frontline of biodiversity conservation and have high intrinsic value. We assessed field stations’ conservation return on investment and explored the impact of COVID-19. We surveyed leaders of field stations across tropical regions that host primate research; 157 field stations in 56 countries responded. Respondents reported improved habitat quality and reduced hunting rates at over 80% of field stations and lower operational costs per km2 than protected areas, yet half of those surveyed have less funding now than in 2019. Spatial analyses support field station presence as reducing deforestation. These “earth observatories” provide a high return on investment; we advocate for increased support of field station programs and for governments to support their vital conservation efforts by investing accordingly
Keywords: Biodiversity; Climate change; Conservation funding; Field stations; Pandemic; Primate-range countries; Protectedareas; Return on investment; Sustainability